PENINGKATAN MOTIVASI DAN HASIL BELAJAR KIMIA SENYAWA HIDROKARBON MELALUI MODEL PEMBELAJARAN LEARNING CYCLE 5 FASE (LC5F) - rukisworo, lilik (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2023)
ABSTRACT Rukisworo, Lilik. 2021. Increasing Motivation and Learning Outcomes in Chemistry of Hydrocarbon Compounds through the Learning Cycle 5 Phase Learning Model. Journal. Abstract: Based on observations during teaching in class XI MIPA 2 SMA Negeri 5 Malang, students tend to experience difficulties in learning hydrocarbons. During learning, students are less motivated to do questions from the teacher, and are often confused in naming alkanes, alkenes, and alkynes if the structural formula is known. A learning model that can involve students to be active in learning and able to construct knowledge properly and correctly is needed in this case. Leraning Cycle learning model to increase students' motivation and learning outcomes. Because in learning using the Learning Cycle learning model, students can be actively involved in the learning process and students must construct their own knowledge. So in this case students are required to find their own concepts. The impact of the application of this learning model has been able to improve the learning outcomes of students in studying hydrocarbon compound material from 44% before the application of the model to 96% in cycle I and 100% in cycle II. The significant increase in cognitive learning outcomes is because in learning using the Learning Cycle learning model, students are required to find their own concepts with the guidance of LKPD, handouts, and guidance from the teacher. This is what makes the concept of hydrocarbons obtained by students really stick in the brain (good retention). The application of the Learning Cycle 5 Phase learning model in this study also increases the learning motivation of XI MIPA 2 class students in learning the material of hydrocarbon compounds. In cycle I there were 48% of students had motivated criteria and 52% of students had very motivated criteria. In cycle 2 there were 35% of students who had motivated criteria, and 65% of students had very motivated criteria. This shows an increase in the number of learners who are highly motivated. The increase in the number of motivated learners in the study was due to the use of interesting media (mollymood), interesting LKPD and handouts, providing contextual apperception, giving points to active learners, and giving exploration and elaboration time to learners. Keywords: Improvement, Motivation, Learning Outcomes, Learning Cycle 5 Phase ABSTRAK Rukisworo, Lilik. 2021. Peningkatan Motivasi dan Hasil Belajar Kimia Senyawa Hidrokarbon Melalui Model Pembelajaran Learning Cycle 5 Fase. Journal. Abstrak: Berdasarkan hasil observasi selama mengajar di kelas XI MIPA 2 SMA Negeri 5 Malang, peserta didik cenderung mengalami kesulitan dalam belajar hidrokarbon. Pada saat pembelajaran, peserta didik kurang termotivasi untuk mengerjakan soal-soal dari guru, dan sering bingung dalam memberi nama alkana, alkena, dan alkuna jika diketahui rumus strukturnya. Suatu model pembelajaran yang dapat melibatkan peserta didik agar aktif dalam pembelajaran dan mampu mengkonstruk pengetahuan dengan baik dan benar sangat diperlukan dalam hal ini. model pembelajaran Leraning Cycle untuk meningkatkan motivasi dan hasil belajar peserta didik. Karena dalam pembelajaran menggunakan model pembelajaran Learning Cycle, peserta didik dapat dilibatkan secara aktif dalam proses pembelajaran dan peserta didik harus mengkonstruksi pengetahuannya sendiri. Jadi dalam hal ini peserta didik dituntut untuk menemukan sendiri konsep yang ada. Dampak dari penerapan model pembelajaran ini telah dapat meningkatkan hasil belajar peserta didik dalam mempelajari materi senyawa hidrokarbon dari 44% sebelum penerapan model menjadi 96% pada siklus I dan 100% pada siklus II. Naiknya hasil belajar kognitif yang sangat signifikan tersebut karena pada pembelajaran menggunakan model pembelajaran Learning Cycle, peserta didik dituntut harus menemukan konsep sendiri dengan bimbingan LKPD, handout, maupun bimbingan dari guru. Hal tersebut yang menjadikan konsep hidrokarbon yang didapat oleh peserta didik benar-benar melekat di otak (retensinya bagus). Penerapan model pembelajaran Learning Cycle 5 Fase pada penelitian ini juga meningkatkan motivasi belajar peserta didik kelas XI MIPA 2 dalam mempelajari materi senyawa hidrokrabon. Pada siklus I terdapat 48% peserta didik memiliki kriteria termotivasi dan 52% peserta didik memiliki kriteria sangat termotivasi. Pada siklus 2 terdapat 35% peserta didik memiliki kriteria termotivasi, dan 65% peserta didik memiliki kriteria sangat termotivasi. Hal tersebut menunjukkan kenaikan jumlah peserta didik yang sangat termotivasi. Naiknya jumlah peserta didik yang termotivasi pada penelitian disebabkan karena penggunaan media yang menarik (mollymood), LKPD dan handout yang menarik, pemberian apersepsi yang kontekstual, pemberian point untuk peserta didik yang aktif, serta pemberian waktu exploration dan elaboration kepada peserta didik. Kata Kunci : Peningkatan, Motivasi, Hasil Belajar, Learning Cycle 5 Fase